2016
DOI: 10.1016/j.jcsr.2016.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Full-field measurement of residual strains in cold bent steel plates

Abstract: With the recent American Association of State Highway and Transportation Officials bridge design code acceptance of cold bent fracture-critical and nonfracture-critical plates and the increasing use of cold bending by the bridge industry, there is a need to better understand and predict residual strains in cold bent steel. However, measuring residual strains is a challenging task since the bending process typically interferes with conventional instrumentation. This paper introduces three-dimensional Digital Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The 2D-FE techniques adopted the plane strain assumption and presumed linear stress in the through-thickness distribution along the corner zone. In contrast, the study showed that the stress distribution in through-thickness direction along the corner zone is not linear [23,24].…”
Section: Transverse Stressesmentioning
confidence: 81%
See 1 more Smart Citation
“…The 2D-FE techniques adopted the plane strain assumption and presumed linear stress in the through-thickness distribution along the corner zone. In contrast, the study showed that the stress distribution in through-thickness direction along the corner zone is not linear [23,24].…”
Section: Transverse Stressesmentioning
confidence: 81%
“…Then, Abambres and Quach [22] stated that the prediction of residual stress along the corner region is neglected in the literature due to the lack of investigations experimentally and numerically in order to verify the stress distribution along the region. Gerbo et al [23] performed 2D and 3D finite element modelling (FEM) to validate the new non-destructive approach measuring residual strains of cold-bent thick plate steel. They recommended a 3D-finite element for detailed investigation.…”
Section: Introductionmentioning
confidence: 99%
“…coated steel (Scenario B, measurements taken on uncoated side, one specimen tested due to availability of coated material), and (c) 12.7‐mm‐thick (0.5 in.) bare steel (Scenario C, eight specimens tested from two different bars, testing performed in Gerbo et al) using 50.8‐mm (2‐in.) gauge length coupons at full thickness (Figure , Table ).…”
Section: Experimental Programmentioning
confidence: 99%
“…Gerbo et al. [9] introduced 3D digital image correlation (DIC) as a new nondestructive approach for measuring residual strains in press-braked thick steel plate with small bending angle (≤30°). He performed 2D and 3D FEM to validate the new approach and recommended 3D-FE for detailed investigation.…”
Section: Introductionmentioning
confidence: 99%